The prevalence and distribution of Brucella melitensis in goats in Malaysia from 2000 to 2009 - Bamaiyi, P. H.; Hassan, L.; Bejo, S. Khairani; M., Zainal Abidin; Ramlan, M.; Adzhar, A.; Abdullah, N.; N. H. M., Hamidah; M. M., Norsuhanna; Hashim, S. N. (Elsevier, 2015)
A study was conducted to describe the prevalence and distribution of zoonotic Brucella melitensis in goats in Peninsular Malaysia. Using serosurveillance data of the last decade (2000–2009) involving 119,799 goats and 3555 farms, the seroprevalence of brucellosis among goats was 0.91% (95% CI = 0.86–0.96) and among farms was 7.09% (95% CI = 6.27–7.98). The odds of brucellosis was significantly (P < 0.05) higher in the later part of the decade, in larger herd size and among the states located in the peninsula as compared to eastern Malaysia. The infection was detected throughout Malaysia but at generally low seroprevalences with states like Perlis that border neighbouring countries having higher seroprevalence of brucellosis than other non-border states.